2009
DOI: 10.1016/j.ejcts.2008.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin protects from reperfusion-induced myocardial injury by enhancing coronary endothelial nitric oxide production☆☆☆

Abstract: Intravenous administration of rhEpo protects the heart against cold global I/R. Apoptosis does not seem to play a major role in the process of tissue injury in this model. After binding to the coronary endothelium, rhEpo enhances NO production by phosphorylation and thus activation of eNOS in coronary vessels. Our results suggest that cardioprotective properties of rhEpo are at least partially mediated by NO released by the coronary endothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 24 publications
1
31
0
1
Order By: Relevance
“…These effects of Epo were confirmed for isolated cells as well as in vivo in hearts after intravenous Epo administration. In the latter case Akt and eNOS phosphorylation is restricted to the endothelial cells of coronary vessels (147). In cardiomyocytes the direct cytoprotective effect of Epo is mediated by its regulatory action on calcium handling and stabilization of the mitochondria.…”
Section: Epor In the Heartmentioning
confidence: 99%
See 2 more Smart Citations
“…These effects of Epo were confirmed for isolated cells as well as in vivo in hearts after intravenous Epo administration. In the latter case Akt and eNOS phosphorylation is restricted to the endothelial cells of coronary vessels (147). In cardiomyocytes the direct cytoprotective effect of Epo is mediated by its regulatory action on calcium handling and stabilization of the mitochondria.…”
Section: Epor In the Heartmentioning
confidence: 99%
“…Whether long term Epo treatment causes similar effects remains unclear. Epo binding to its receptors induces phosphorylation of Akt and eNOS -its effects are seen within 5 min (147) and can be observed for the first hour and thereafter the Epo-EpoR complex is internalized and degraded (Mihov, Tavakoli, Bogdanova unpublished observations). The internalization rate constant for Epo-EpoR complex in UT-7/Epo cells is 0.06 min −1 (172).…”
Section: Epor In the Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide (NO) availability is a crucial element in the protection of the heart from hypoxic injury. NOSs are known as O 2 sensors and are capable of generation of both antioxidative and cytoprotective NO, and superoxide anion, giving rise to prooxidative hydrogen peroxide and hydroxyl radical (Mihov et al 2009a(Mihov et al , 2009b. Generation of NO is an oxygen-dependent process because oxygen is a substrate of NOSs along with l-arginine.…”
Section: Rescuing the Hypoxic Heart: Nitrite And No In Cardioprotectionmentioning
confidence: 99%
“…Animal studies have shown that cardio and neuro protection occur when EPO is administered for preconditioning strategy or administered during resuscitation from cardiac arrest as well as reduced prevalence of arrhythmias when given prior to focal I/R. (67,(70)(71)(72)(73)(74)(75) EPO administered during cardiac arrest and resuscitation in early human trials appears encouraging. (76)(77) …”
Section: Methods For Stimulating and Interacting With The Endotheliummentioning
confidence: 99%